2019
DOI: 10.1007/s42380-019-00029-3
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Victimization Among Asian-American Youth: a Review of the Literature

Abstract: Bullying is a significant public health and social problem in the United States. As a fast-growing immigrant population, Asian-American youth are being bullied at school, yet little is known about their experience in bullying victimization. Thus, the purpose of this article is to review current findings regarding bullying victimization among Asian-American youth. A review of the literature was conducted. Twenty-three articles that met the inclusion criteria were included in the present review. The research tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 52 publications
(136 reference statements)
0
6
0
1
Order By: Relevance
“…From this perspective, in order to feel motivated and achieve their highest academic potential, all these three needs must be supported in students. Negative school conditions such as peer rejection, social exclusion, and bullying may undermine these needs [ 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this perspective, in order to feel motivated and achieve their highest academic potential, all these three needs must be supported in students. Negative school conditions such as peer rejection, social exclusion, and bullying may undermine these needs [ 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, bullying victimisation has been found to negatively influence students’ school relatedness, such that bullied students tend to feel less connected to their school and, in turn, tend to achieve poorly academically [ 43 ]. On top of this, students who have suffered bullying victimisation present lower academic motivation, reduced perceived academic competence [ 21 ] and lower educational aspirations [ 31 ] in comparison to their non-bullied peers.…”
Section: Introductionmentioning
confidence: 99%
“…A population data analysis spanning 2001 to 2011 found that Asian American boys were targeted by racist verbal assaults more frequently than their peers across gender and race (Cooc & Gee, 2014). Among Asian American youth, boys are more likely to be peer-victimized, especially physically (Huang & Vidourek, 2019). Large-scale studies including this group have linked peer-victimization with substance use (Stone & Carlisle, 2017) and suicidality (Wang et al, 2018), both of which are significant public health problems for AAM (Hai et al, 2021; Keum & Choi, 2022; Ramchand et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear as to why the reduction effect of racial/ethnic bullying alone on the association between ethnicity and substance use was either less noticeable or not observed. A recent review on bullying victimization among Asian American youth suggests that racial/ethnic bullying victimization is indeed associated with adverse outcomes, including mental health and academic performance (Huang & Vidourek, 2019). It is possible that, without taking Asian American youth's sexual orientation into consideration, their substance use behaviors are more affected by other racial/ethnic contextual factors such as peer use, which is heavily impacted by peer immigrant generation status and peer ethnicity (Ryabov, 2015).…”
Section: Discussionmentioning
confidence: 99%